University Students’ Willingness to Communicate in Virtual Classroom - Hanifah Hanifah; Elsa Ernawati Nainggolan (Ahmad Dahlan Journal of English Studies, 2021)
Shifting from real classes to online classes ideally does not decrease students’ willingness to communicate (WTC) in a language classroom since it is an indication of successful language learning in a virtual class. Given the crucial of promoting students’ willingness to communicate in English online class, the present study analyzed the patterns of university students’ WTC in a synchronous virtual class. With this purpose in mind, 43 students taking English for general purposes were chosen as the sample in this study. To gather the data of students’ WTC patterns, the online class using zoom application was observed by administrating the Coding scheme developed by Chao and Philp. The patterns of the students’ WTC were analyzed and classified into six categorizes based on the scheme. The results of the study reveal that the occurrences and patterns of students’ WTC are affected by different task types given by the lecturer. Thus, it is expected that education practitioners construct virtual learning design providing various activities so that students’ WTC in an online classroom can be triggered and enhanced.